Sudan's HIV Response : Value for Money in a Low-Level HIV Epidemic - Fraser, Nicole; Benedikt, Clemens; Obst, Michael; Masaki, Emi; Görgens, Marelize; Stuart, Robyn; Shattock, Andrew; Gray Richard; Wilson, David (World Bank, Washington, DC, 2015)
This report summarizes the findings of an allocative efficiency analysis on Sudan s national HIV epidemic and response conducted in 2014. HIV allocative efficiency studies are generally trying to answer the question How can HIV funding be optimally allocated to the combination of HIV response interventions that will yield the highest impact . In the first half of 2014, the Sudan National AIDS Programme has reviewed its national strategic plan (NSP) on HIV and AIDS, while at the same time preparing a concept note for submission to the Global Fund for AIDS, Tuberculosis and Malaria, the single largest funding partner of the national HIV response. In this context the government of Sudan approached the World Bank with a request to conduct an allocative efficiency analysis to inform both the prioritization of the national HIV response and the concept note development.